SOUTH AFRICA AND REGIONAL STABILITY IN THE MBEKI ERA: THE NEXUS BETWEEN PERSONALITY AND GEO-POLITICAL AND ECONOMIC CONCERNS IN FOREIGN POLICY MAKING - Akanji, Olajide Olayemi (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This paper examines the role that South Africa during Mbeki’s presidency played in peace and security issues of Southern African Development Community (SADC). The paper infers that South Africa under Mbeki adopted a peace-building approach, comprising mediation, negotiation, peacekeeping, promotion of democracy and election monitoring, in addressing peace and security challenges in the SADC. It however argues that it was the person of Mbeki, shaped by his leadership and revolutionary experiences in the African National Congress (ANC) during apartheid era, alongside South Africa’s economic strength that underlined and shaped its approach and contributions to SADC peace and security.